Encyclopedia of Mathematical Physics 2006
DOI: 10.1016/b0-12-512666-2/00316-3
|View full text |Cite
|
Sign up to set email alerts
|

Hopf Algebra Structure of Renormalizable Quantum Field Theory

Abstract: Renormalization theory is a venerable subject put to daily use in many branches of physics. Here, we focus on its applications in quantum field theory, where a standard perturbative approach is provided through an expansion in Feynman diagrams. Whilst the combinatorics of the Bogoliubov recursion, solved by suitable forest formulas, has been known for a long time, the subject regained interest on the conceptual side with the discovery of an underlying Hopf algebra structure behind these recursions.Perturbative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…In the case of the overlapping divergences, at the first step they should be reduced to a linear combination of disjoint and nested divergences and next we have a sum of rooted trees [21,26]. Depends on a fixed theory, all rooted trees are equipped with specific decorations (which store physical information such as (sub)-divergences) [12,20,22,23]. Renormalization Hopf algebra of a given theory can be made based on a decorated version of an interesting Hopf algebra structure on rooted trees and in this part this Hopf algebra is studied.…”
Section: Connes-kreimer Hopf Algebra Of Rooted Treesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of the overlapping divergences, at the first step they should be reduced to a linear combination of disjoint and nested divergences and next we have a sum of rooted trees [21,26]. Depends on a fixed theory, all rooted trees are equipped with specific decorations (which store physical information such as (sub)-divergences) [12,20,22,23]. Renormalization Hopf algebra of a given theory can be made based on a decorated version of an interesting Hopf algebra structure on rooted trees and in this part this Hopf algebra is studied.…”
Section: Connes-kreimer Hopf Algebra Of Rooted Treesmentioning
confidence: 99%
“…Therefore the lack of a practical mathematical basement for this interesting physical technique in QFT is covered. [1,20,21,22,23,24,25] Connes and Kreimer proved that perturbative renormalization can be explained by a general mathematical procedure namely, extraction of finite values based on the Riemann-Hilbert problem and in this way they showed that one can obtain the important physical data of a renormalizable QFT for instance renormalized values and counterterms from the Birkhoff decomposition of characters of the related Hopf algebra to the theory. In other words, they associated to each theory an infinite dimensional Lie group and proved that in dimensional regularization passing from unrenormalized to the renormalized value is equivalent to the replacement of a given loop (with values in the Lie group) with the value of the positive component of its Birkhoff factorization at the critical integral dimension D. In fact, in [2,3] an algebraic reconstruction from the Bogoliubov-Parasiuk-Hepp-Zimmermann (BPHZ) method in renormalization is initiated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a strictly perturbative viewpoint, this is summarized in this volume in the paper by Ebrahimi-Fard and Guo [3], with emphasis given to Rota-Baxter algebras. Our own summary below follows [4]. We hence will be short in our discussion of the perturbative viewpoint, and aim at a qualitative discussion of the above points, exemplified in the much stressed example of the propagator in massless Yukawa theory [5,6].…”
Section: Introductionmentioning
confidence: 99%